Diagnosis of Epilepsy: from the Beginning to the New Hybrid PET/MR Technique - Igor A. Znamenskiy; Mikhail B. Dolgushin; Anastasiya A. Yurchenko; Tatiana M. Rostovtseva; Mariya A. Karalkina (Клиническая практика, 2023)
The problem of diagnosis and treatment of epilepsy concerns medical society for a several thousands of years. The understanding of the causes and pathological mechanisms of this condition underwent numerous and substantial changes during this time, that allowed reaching significant advances in both the diagnosis or treatment. At the present time, there is a wide spectrum of diagnostic methods that allow localizing the epileptogenic focus, that is essential for planning the surgical treatment in patients with pharmacoresistant epilepsy. The results of the surgical treatment are strongly dependent on the diagnostic accuracy in the detection of one or several epileptogenic foci and on the prognosis of their resection. In this connection, the research on the possibilities and perfection of new diagnostic methods hold the potential to improve the results of the surgical treatment and the life quality in patients with pharmacoresistant epilepsy. This review presents a detailed description of the evolution of epilepsy diagnostics from the first implementation of electroencephalography in the 1920-s to the modern hybrid methods such as SISCOM (Subtraction Ictal SPECT Co-Registered to MRI) and PET-MRI.